A study to evaluate willingness to pay using Van Westendorp’s method on the example of contraceptives - Mahanova, T. V.; Tkachenko, N. A.; Popovych, V. P.; Маганова, Тамара Валеріївна; Ткаченко, Наталя Олександрівна (My University, 2022)
Family planning remains one of the key areas of healthcare that needs significant support regardless of country. The preservation of a woman’s health through the use of contraceptives until she is fully ready for childbirth prevents a number of social and economic cataclysms: demographic, labor, and other kinds of crises. However, in modern conditions of limited healthcare resources, as well as economic difficulties faced by women, there is a need to improve the provision of contraceptives to women in family planning. The purpose of that is primarily to reduce the economic burden on the state and women, as well as patient orientation.Therefore, the determination of willingness to pay for contraceptives is critical in the improvement of family planning systems. The study’s aim was to develop and test Van Westendorp’s method for establishing willingness to pay in Ukraine followed by the sharing of the economic burden between women and the state in family planning programs. A cross-sectional study involved a hall test with an anonymous questionnaire survey. Descriptive statistics and regression modeling were used. It was established that for women with an income of up to 88 EUR the acceptable price range made up from 26% to 38% of the price values; for women with an income of 88–129 EUR, from 30% to 48%; and for women with an income of more than 129 EUR, from 32% to 51%. Similarly, willingness to pay was calculated for all contraceptives in age groups. These findings suggest that the willingness to pay for contraceptives is relatively low in Ukraine. This information can be used to construct a payment model for contraceptives and to attain higher contraceptive coverage, especially for those who are less wealthy.
Keywords: Willingness to pay; health economics; contraceptive; Van Westendorp’s method